Hormone use and abuse by athletes - Ghigo, E. (Ezio); Lanfranco, Fabio; Strasburger, Christian J. (Endocrine updates, 2011)
Several hormones are able to influence physical performance and body composition. Thus, a bi-univocal interrelationship between exercise and hormones exists. In Hormone Use and Abuse by Athletes, new developments on metabolic and endocrine responses to exercise are revised and the topic of hormonal doping in sports is introduced. In the past decades, hormone abuse has become a widespread habit in professional and?most of all and more frequently?recreational performance. Anabolic steroids, growth hormones and erythropoietin properties use and misuse in sports are widely described. Specific methods to detect hormone abuse are presented and discussed. The contributors to this volume are well-known experts and dedicated researchers in the fields of sports medicine and endocrinology, endocrine physiology, pharmacology, and doping detection. The purpose of this volume is to provide all professionals involved in sports medicine and endocrinology a state-of-the-art overview of the complex interactions between physical activity and the endocrine system and to focus on hormone abuse in sports at competitive and recreational levels, highlighting its negative consequences for long-term health. "In this very topical volume, the editors have assembled an expert panel of authors addressing one of the most significant challenges in sports medicine today?the use and abuse of hormones in competitive sports. The chapters provide up-to-date, clearly written information ranging from physiology of the pituitary axes in exercise and sports, impact of reproductive function illicit hormonal abuse, and assay methods and compelling pitfalls for rigorous detection of sports doping. This volume will be of great utility to sports physicians, exercise physiologists and endocrinologists, as well as to scientific and sports regulatory agencies and ethicists grappling with responding to this societal challenge." - Shlomo Melmed, M.D. Series Editor.